Reactive T Cells in Convalescent COVID-19 Patients With Negative SARS-CoV-2 Antibody Serology - Steiner, Sophie; Schwarz, Tatjana; Corman, Victor M.; Sotzny, Franziska; Bauer, Sandra; Drosten, Christian; Volk, Hans-Dieter; Scheibenbogen, Carmen; Hanitsch, Leif G. (Frontiers in Immunology, 2021)
Despite RT-PCR confirmed COVID-19, specific antibodies to SARS-CoV-2 spike are undetectable in serum in approximately 10% of convalescent patients after mild disease course. This raises the question of induction and persistence of SARS-CoV-2-reactive T cells in these convalescent individuals. Using flow cytometry, we assessed specific SARS-CoV-2 and human endemic coronaviruses (HCoV-229E, -OC43) reactive T cells after stimulation with spike and nucleocapsid peptide pools and analyzed cytokine polyfunctionality (IFNγ, TNFα and IL-2) in seropositive and seronegative convalescent COVID-19 patients as well as in unexposed healthy controls. Stimulation with SARS-CoV-2 spike and nucleocapsid as well as HCoV spike peptide pools elicited a similar T cell response in seropositive and seronegative post COVID-19 patients. Significantly higher frequencies of polyfunctional cytokine nucleocapsid reactive CD4+ T cells (triple positive for IL2, TNFα and IFNγ) were observed in both, seropositive (p = 0.008) and seronegative (p = 0.04), COVID-19 convalescent compared to healthy controls and were detectable up to day 162 post RT-PCR positivity in seronegative convalescents. Our data indicate an important role of NCAP-specific T cells for viral control.